Bringing Nordic Slush to Asia : entrepreneurial internationalization of an NGO as a social movement - Galkina, Tamara; Yang, Man (Elsevier, 2020)
We explore the internationalization of Slush, an entrepreneurship-promoting NGO from Finland that expanded to Japan, China, and Singapore. We incorporate the social movement theory that allows revealing special mechanisms of NGOs’ internationalization. We show, first, that international opportunity development of internationalizing NGOs is triggered by the shared dissatisfaction with societal conditions. Second, their collective resource mobilization enables networks and learning in foreign markets. Third, internationalizing NGOs overcome internationalization liabilities through building their social identities. We also offer a model of NGO internationalization that incorporates the social movement theory. Overall, our study broadens internationalization research by bringing a non-business theory into it.
Keywords: internationalization; social movement theory; NGOs; Finland; fi=Kansainvälinen liiketoiminta|en=International Business|